IDEOLOGICAL REPRESENTATION THROUGH NOUNS IN THE QUESTION OF RED AND ITS SELF-TRANSLATION AMBA - Andy Bayu Nugroho; Myrna Laksman Huntley; Rahayu Surtiati Hidayat (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2021)
Literary translation are often faced with problems of equivalence, faithfulness, accuracy, and naturalness. This becomes more complex because the author can choose between many options. Therefore, the author’s choice of style has roles in representing his ideology. This study discusses literary translation by the author herself. This study aims at explaining whether the case of self-translation of the novel The Question of Red (TQOR) and Amba experienced distinction in the lexical category of style markers which led to a potential difference in the self-translator's ideology. A qualitative research method with Fairclough's critical discourse analysis approach was used to reveal the ideological representation. The data sources are an English novel, TQOR, and its Indonesian translation, Amba. The research data are nouns in source text and their translation which represent the self-translator’s ideology. The analysis followed Fairclough’s model of description, interpretation, and explanation. The results show that the ST has more nouns as the lexical style markers than the TT. In both texts, abstract nouns are used more frequently than concrete nouns which offers more affective involvement so that the readers of both texts can feel the experience of the characters rather than giving sensory perceptions to the readers. Keywords: ideological representation, style markers, nouns, self-translation AbstrakPenerjemahan karya sastra selalu dihadapkan pada permasalahan kesepadanan, kesetiaan, keakuratan, dan kealamiahan yang dapat menjadi lebih rumit karena pengarang dapat menggunakan gaya bahasa yang khusus. Penelitian ini membahas kasus penerjemahan karya sastra yang dilakukan oleh pengarangnya sendiri (swaterjemah). Penelitian ini bertujuan melihat apakah kasus swaterjemah novel The Question of Red (TQOR) dan Amba mengalami pergeseran gaya bahasa kategori leksikal yang mengarah pada potensi pergeseran ideologi pengarang-penerjemah. Metode penelitian kualitatif dengan analisis wacana kritis Fairclough digunakan untuk mengungkap ideologi pengarang-penerjemah. Sumber data berupa novel berbahasa Inggris, TQOR, dan terjemahan bahasa Indonesianya, Amba. Data penelitian adalah nomina di dalam TSu dan terjemahannya dalam TSa yang merepresentasikan persepsi ideologis pengarang-penerjemah. Analisis menggunakan model AWK Fairclough, yaitu deskripsi, interpretasi, dan eksplanasi. Hasil penelitian menunjukkan bahwa TSu memiliki lebih banyak pemarkah gaya bahasa kategori leksikal nomina daripada TSa. Pada kedua teks, nomina abstrak lebih banyak digunakan daripada nomina konkret. Dengan demikian pengarang-penerjemah lebih menawarkan keterlibatan afektif agar pembaca turut merasakan pengalaman tokoh-tokohnya daripada memberikan persepsi indrawi. Kata Kunci: representasi ideologis, gaya bahasa, nomina, swaterjemah